Analysis of Automation Processes of Printed Circuit Boards Manufacturing Equipment - Klepach, Marko; Klepach, Mykola; Kozak, Leonid (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
In this article, the authors present a process of the printed circuit boards manufacturing equipment simulation model design. The model was used to create, optimize and test the movement control subsystem of the device.